Análisis comparativo del uso del tiempo por algunos agentes agrícolas en Venezuela - Chacin Medina, Guillermo R. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A sample of six agricultural agents in Venezuela to determine their use of time. An observation guide allowed checking several topics every five minutes and a questionnaire was used to determine the opinions of effective use of time. Results indicate that agents use a higher percentage of their time in the office and less time in the form and homes of the farmers. Time consumed in non-educational activities (64%) is higher in relation to time spent in educational activities (36%). In regard to effective use of time, the informants consider that the agents should employ their time in the farms, offices, and homes of the farmers; leaders and rural youth; and that more time should be spent on agricultural activities than in other activity. Other topics are discussed and recommendations are made